Karakterisasi Genotipe F1 dan F2 Jagung Varietas Srikandi Putih dan Lokal Pulut Pada Jarak Tanam yang Berbeda - Edy Edy (Agrosains : Jurnal Penelitian Agronomi, 2020)
The crossing between Srikandi Putih corn varieties which have high production potential and protein content with local pulut corn which has high amylopectin levels is expected to produce superior offspring. This study aimed to determine the character of F1 and F2 results of crossing of Srikandi Putih variety with local Pulut corn (waxy corn) at different planting distance. This research was conducted in the Experimental Farm of the Bajeng Cereals Crop Research Institute, South Sulawesi Province, from May-August 2018. This method used was Split Plot Design, consisting of Main Plots, namely planting distance (70 cm x 20 cm and 70 cm x 30 cm) and Sub Plots, namely Varieties (Srikandi Putih, Local Pulut, F1 and F2). The results showed that genotype significantly affected plant height, seed production per hectare, amylopectin content and seed protein content, and genotype had very significant effect on number of leaves, ear length, ear diameter, seed weight per plant and seed weight per plot. Planting distance has a very significant effect on seed weight per plot and the best was 70 cm x 20 cm. This is due to the number of populations at 70 cm x 20 cm planting distance more than 70 cm x 30 cm. Genotype interaction and planting distance have a very significant effect on seed weight per plant. Srikandi Putih variety was the best genotype for growth, production and protein content parameters while the best amylopectin content parameter was local Pulut. Srikandi Putih variety was potential for growth and production as well as high protein content, but low amylopectin levels while local Pulut has high potential for amylopectin levels but low growth and production potential. The best combination of growth, production, protein and amylopectin content was in F1 and F2 genotypes.